The Lighthouse Mystery : The Boxcar Children # 8 - Gertude Chandler Warner (U.S.A Scholastics)
Renting a lighthouse is unusual, but even more so is an unfriendly boy's peculiar behavior.
Keywords: Mystery -- Mystery